Response of yield and quality of giant embryo rice to nitrogen application and analysis of lipid-lowering effect - Hu, Mingming; Chen, Guangyi; Peng, Ligong; Li, Congmei; He, Xingmei; Zhang, Qiuqiu; Yang, Hong; Liang, Chaode; Kuang, Hudong; Lan, Yan; Li, Tian (Frontiers in Plant Science, 2022)
Giant embryo rice is known as a highly nutritious functional rice because it is rich in gamma-aminobutyric acid (GABA), which has various regulatory functions in the human body. To study the response of giant embryo rice yield and quality to nitrogen (N) application, and to verify the effect of giant embryo brown rice on alleviating hyperlipidemia in rats. In this study, field experiments were conducted in 2020 and 2021 using the giant embryo rice varietiers J20 (japonica) and Koshihikari (japonica) rice as experimental materials and five N levels, 0 (N0), 90 (N1), 135 (N2), 180 (N3) and 225 (N4) kg ha-1. The results showed that the yield of both varieties increased with increasing N and the maximum values were observed under the N2 treatment. As more N was gradually applied, the brown rice rate, milled rice rate, head rice rate and GABA content of both varieties first increased and then decreased, while the chalky grain rate and chalkiness showed the opposite trend. The optimal values of these indexes were observed under the N2 treatment. The peak viscosity and breakdown value of J20 decreased, while its setback value and pasting temperature increased with increasing N. In contrast, Koshihikari showed the opposite trend. The protein content and protein component contents of both varieties showed an increasing trend with increasing N, among which gliadin was the most sensitive protein component to N fertilizer. Animal experiments results showed that J20 brown rice could significantly slow the rate of weight gain of rats, reduce serum total cholesterol and triglyceride levels and increase high-density lipoprotein cholesterol levels. Therefore, increasing N could effectively enhance J20 yield and improve processing, appearance and nutritional quality but decrease cooking and eating quality. The brown rice J20 had the effect of slowing the rate of weight gain and reducing the hyperlipidemia level of rats, the optimal N application rate for achieving high yield, high quality and good functional characteristics in the giant embryo rice J20 was 135 kg ha-1. These findings will provide a theoretical and technical foundation for the popularization and application of giant embryo rice in the future.